Participatipatory Democracy and Citizen’s Involvement - M.P. Shegunashi, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Democracy stands on people’s participation, civilians’ active participation is the strength of the democratic form of government. It highlights extensive, direct public participation in state decision making as in cooperation of standardizing ideal and set of institutional practice. This paper highlighted foremost academic traditions like classical participatory approaches, “strong democracy”, and empowered participatory administration, reviews observed indication from influential cases, deliberates devices linking participation to deliberation, capacity building, redistribution, and outlines an experimental design to evaluate participatory reforms. The analysis treasures well considered participatory institutions can increase civilian involvement, improve public goods targeting, and reinforce democratic rightfulness, nevertheless effects vary by institutional design, context, and scale. Policy implications and directions for further research are offered.
Keywords: Democracy; Participation; Institutions; Civic involvement